Estudo da dinâmica da fermentação em processo batelada e semicontínuo para produção de etanol - Silva, Carolina Leite da (2016)
Ethanol is a renewable energy source and it is considered one of the best alternatives to climate change caused, in part, by the use of fossil fuels. Biotechnological processes are primarily responsible for the worldwide production of ethanol. In this work the ethanol production by Saccharomyces cerevisiae yeast in a batch and semi-continuous reactor was studied with the objective of analyzing the dynamics of this fermentation process. This study was carried out though de proposition of mathematical models capable of predicting the behavior of the biomass, substrate and product concentration along the fermentation time, as well as estimating the parameters of the proposed models. The fermentation process was carried out in an isothermal bioreactor with a working volume equal to 1 L, at a temperature of 32 °C, under agitation of 175 rpm and pH equal to 3.0. The fermentation time was equal to 15 h for the batch process and 60 h for the semi-continuous process. For the study of the batch reactor, five models were proposed, in which the variations with time of the biomass, substrates and product concentrations were based on the mass balance for each component in the reactor. In the first model the fermentation kinetic was based on the classical kinetic proposed by Monod; in the second it was based on microbial kinetic weighted by the maximum concentration of microorganism; the third model was proposed in an attempt to predict the behavior of cell decay observed experimentally; in the fourth model the microbial growth was weighted by the maximum concentration of product; and finally, the fifth model took into account parameters of substrate consumption and formation of product by the yeasts. The model evaluated to predict the behavior of the semi-continuous fermentation was based on the proposed mass balance for this bioreactor, along with the Monod kinetic equation. All the models were implemented in FORTRAN, solved with the application of the DASSL subroutine and the kinetic parameters of each model were estimated through the ESTIMA program, where the objective function was least squares. The lowest value found for the objective function was the criterion adopted to choose the model that best fit the experimental data. In the batch reactor the classic model proposed based on the Monod kinetics was the one that presented the best fit to the experimental data and the value of the objective function was 0.5291. The estimated values of the parameters of this model were statistically significant and physically realistic and accurately described the experimental data: µmáx = 0.1155 h-1 ; K1 = 0.8984 h-1 ; K = 0.4738 h-1 ; YX/S = 0.0242; YX/P = 0.0451 e KS = 24.3852 g‧L -1 . The estimated parameters for the semicontinuous bioreactor were also physically realistic and statistically significant and their values were: μmáx = 0.1195 h-1 ; K1 = 0.3999 h-1 ; K = 0.2725 h-1 ; YX/S = 0.0102; YX/P = 0.0207 e KS = 121.6581 g‧L -1 ; the objective function value was equal to 7.475. The results indicate that the semi-continuous bioreactor can be used in alcoholic fermentation, and it can operate for longer times than those reported for the batch bioreactor operating under the same conditions, without the need to prepare a new inoculum. The results also suggested the possible occurrence of cell wash out during the discharge and recharge process, which could be avoided by recycling these cells.